Physical Activity Analysis and Comparison of Secondary School Students in Terms of Selected Regions of Slovakia: A Cross-Sectional Study - Štefan Adamčák; Gabriel Bujdoš; Michal Marko; Karol Görner (Sport i Turystyka, 2022)
Accumulating evidence indicates that regular physical activity plays an important role in strengthening health, however, its absence causes a loss of physical fitness and organism endurance. Our study was aimed at analysing and comparing physical activity of secondary school students in terms of selected regions of Slovakia. A cross-sectional survey measuring (January – December, 2021) physical activity was conducted through intentional sampling with the survey size of 1829 secondary school students (aged 17.35 ± .82) who attended the last year (4th) of grammar and vocational secondary schools. Each answer of the survey group was analysed, compared and evaluated by using the chi-square test (χ2) with the significance level (α) of .01 and .05. After analysing the survey answers, on average, 54.24 % (n = 902) of the survey group indicated the recreational form of physical activity (p < .01). In terms of the main place of performing physical activity, the survey answer of “Indoor (Gym, hall...)” covered 43.95 % (n = 804) of the survey group (p < .01). Physical activity of secondary school students varies depending on the region, while it is necessary to apply effective out-of-school physical activity programmes to increase the volume of physical activity of secondary school students.